Inventory Information System Design at PT. Instaprint Jaya Primatama - Saputro, Janu Ilham; Octavia, Dwiana; Wibisono, Hurdjanto (Pandawan Sejahtera Indonesia, 2020)
Information technology is rapidly developing all existing activities or activities become very important in determining the progress of the company, both in operational and non-operational activities, one of which is the procurement report which must produce accurate and accurate reports. PT Instaprint Jaya Primatama is a company engaged in the field of digital printing while those who do not yet have a system that uses stock of goods, the current system still has problems such as requiring a long time to find the amount needed Every day and making reports still using Ms. Excel so there is a delay in the company's performance. This study aims to create a system that can support the process of reporting needs that can be done effectively, the design process uses the PIECES method, system modeling using UML (Unified Modeling Language) to use visualization, which can be used by using the Hypertext Preprocessor programming language (PHP ) with a MySQL-Server database as a database. And to collect data, the authors use the method of observation, interviews, and literature study. With the system of preparation of goods, can make it easier for inventory administrators to produce accurate reports with a fast time can be made in order to produce effective and efficient.